2021
DOI: 10.1002/eap.2236
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of distributions and niches of North American cold‐adapted amphibians: evaluating both climate and land use

Abstract: Species distribution estimates are often used to understand the niche of a species; however, these are often based solely on climatic predictors. When the influences of biotic factors are ignored, erroneous inferences about range and niche may be made. We aimed to integrate climate data with a unique set of available land cover and land use data for the six cold‐adapted amphibians of North America (Ambystoma macrodactylum, Anaxyrus hemiophrys, Anaxyrus boreas, Pseudacris maculata, Rana sylvatica, Rana luteiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 97 publications
2
12
0
Order By: Relevance
“…Because climate and land‐use gradients vary at different temporal scales, and are often correlated over narrow extents of space and time (Oliver & Morecroft, 2014), detecting coherent signals of global change on species’ occurrence requires expansive, long‐term studies that allow for the isolation of spatial versus temporal components of environmental variables (Kelly et al, 2013; Maclean et al, 2008). As a result of these challenges, most studies have either assessed the influence of a single global‐change driver, often climate, over long time periods (Amano et al, 2020; Pearce‐Higgins et al, 2015; Termaat et al, 2019; Tingley et al, 2009) or have fit static models assessing the influence of multiple drivers under the assumption that speciesʼ responses will exhibit stationarity (Seaborn et al, 2021; Vermaat et al, 2017). However, species may not be in equilibrium with their environment at limited spatial and/or temporal scales (Bar‐Massada & Belmaker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because climate and land‐use gradients vary at different temporal scales, and are often correlated over narrow extents of space and time (Oliver & Morecroft, 2014), detecting coherent signals of global change on species’ occurrence requires expansive, long‐term studies that allow for the isolation of spatial versus temporal components of environmental variables (Kelly et al, 2013; Maclean et al, 2008). As a result of these challenges, most studies have either assessed the influence of a single global‐change driver, often climate, over long time periods (Amano et al, 2020; Pearce‐Higgins et al, 2015; Termaat et al, 2019; Tingley et al, 2009) or have fit static models assessing the influence of multiple drivers under the assumption that speciesʼ responses will exhibit stationarity (Seaborn et al, 2021; Vermaat et al, 2017). However, species may not be in equilibrium with their environment at limited spatial and/or temporal scales (Bar‐Massada & Belmaker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some regions classified as newly suitable (i.e., expansion) in future models are currently occupied by modeled species. In their study using climate and land‐use features to assess the spatial patterns of cold‐adapted amphibians, Seaborn et al (2021) reported climate‐only and combination ecological niche models underpredicted the northern edge for high latitude species. Similarly, we suggest underpredicted suitability in northern range limits of current models, sampling bias in occurrence collections, and spatial filtering of localities influenced the climatic range expansion observed for our 2 high‐latitude species (blue‐spotted salamander and red‐backed salamander; Sheridan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our analyses suggest 4 salamander species common across the eastern United States and Canada will experience dramatic range restrictions in response to anthropogenic climate change. While a plethora of factors outside climate (e.g., land use, species interactions, human footprint) influence habitat suitability (Heikkinen et al 2007), researchers report that climate‐only niche models, especially for amphibian taxa, can perform similarly or better than combination models (Bucklin et al 2015, Seaborn et al 2021). By calibrating models with multiple estimations of atmospheric greenhouse gas concentrations, we showed that even a drastic reduction in global emissions will not save the taxa modeled from significant climatic range restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the resultant model may wrongly infer urban land‐use as suitable and underestimate the true impact of deforestation on the species’ range. This situation arises because of the lack of temporal range and resolution for many anthropogenic variables, and conventional use of static predictors in most SDM studies; hence, contemporary anthropogenic variables are often utilized in SDM studies despite possible mismatching with historical occurrences (Garcia et al, 2013; Marshall et al, 2018; Seaborn et al, 2021). Although modelling without anthropogenic variables avoids potential mismatching, where range contractions can be accounted for post‐hoc (see Gomes et al, 2019; Manchego et al, 2017; Newbold, 2018), excluding anthropogenic variables facilitates niche truncation when occurrences are sampled after an ARC.…”
Section: Introductionmentioning
confidence: 99%